Confidentiality And Security Of Health Information: Collaborative Work Between Health Information Management, Health Security, Health Administration, Nursing, Laboratory Services And Medical Secretaries (The Review of Diabetic Studies, 2024)
Confidentiality and security of health information are fundamental ethical, legal, and operational requirements in contemporary healthcare systems. The rapid expansion of electronic health records, laboratory information systems, administrative platforms, and health information exchanges has transformed the way patient data are created, accessed, and shared, while simultaneously increasing vulnerability to unauthorized disclosure, misuse, and cyber threats. Effective protection of health information therefore requires coordinated multidisciplinary collaboration rather than isolated technical or administrative interventions. This review examines confidentiality and security of health information through the collaborative roles of Health Information Management, Health Security, Health Administration, Nursing, Laboratory Services, and Medical Secretaries. It highlights how shared governance, integrated workflows, and role-specific accountability are essential to safeguarding patient information while maintaining data availability and integrity for safe, high-quality care.